Reduced humidity induces skin barrier dysfunction and secretion of dipeptidyl peptidase-4 (DPP-4) in a skin-equivalent model - Lee, Sung Hoon; Bae, Il-Hong; Marinho, Paulo A.; Lee, Chang Seok; Lee, Jongsung (Archives of Biological Sciences, 2019)
Paper description: This study was initiated to provide a better understanding of the effect of humidity on skin. A skin equivalent model (EpiDermTM FT-400) was cultured for 48 h under standard (80%) and reduced (60%) relative humidity, and the barrier function and secreted proteins were analyzed. Reduced humidity damaged the skin barrier, affecting the secretion of several cytokines, notably upregulating dipeptidyl peptidase-4 (DPP4), which has different roles in the immunological process. Abstract: Seasonal changes can affect the physiological condition of the skin and cause various cutaneous disorders. The skin barrier function tends to worsen during winter when humidity is lower compared to other seasons. To determine the influence of relative humidity (RH) on the function of the skin barrier, we performed biological and histological assays using skin equivalents that were cultured under reduced humidity in an environmental humidity chamber. We found that reduced humidity led to decreased epidermal thickness and disruption of the skin barrier. Reduced humidity induced the decrease of filaggrin, loricrin and damage to tight junction. In addition, dipeptidyl peptidase-4 (DPP4), which has roles in the immunological process, was upregulated in a skin-equivalent model under reduced humidity. These results suggest that reduced humidity affects the skin barrier function and regulates the secretion of DPP4 in a skin-equivalent model. https://doi.org/10.2298/ABS190523052L Received: May 23, 2019; Revised: July 25, 2019; Accepted: August 8, 2019; Published online: August 30, 2019 How to cite this article: Lee SH, Bae I, Marinho PA, Lee CS, Lee J. Reduced humidity induces skin barrier dysfunction and secretion of dipeptidyl peptidase-4 (DPP-4) in a skin-equivalent model. Arch Biol Sci. 2019;71(4):697-702.